Application of Job Demands-Resources model in research on relationships between job satisfaction, job resources, individual resources and job demands - Adrianna Potocka; Małgorzata Waszkowska (Nofer Institute of Occupational Medicine, 2013)
Background: The aim of this study was to explore the relationships between job demands, job resourses, personal resourses and job satisfaction and to assess the usefulness of the Job Demands-Resources (JD-R) model in the explanation of these phenomena. Materials and Methods: The research was based on a sample of 500 social workers. The "Psychosocial Factors" and "Job satisfaction" questionnaires were used to test the hypothesis. Results: The results showed that job satisfaction increased with increasing job accessibility and personal resources (r = 0.44; r = 0.31; p < 0.05). The analysis of variance (ANOVA) indicated that job resources and job demands [F(1.474) = 4.004; F(1.474) = 4.166; p < 0.05] were statistically significant sources of variation in job satisfaction. Moreover, interactions between job demands and job resources [F(3,474) = 2.748; p < 0.05], as well as between job demands and personal resources [F(3.474) = 3.021; p < 0.05] had a significant impact on job satisfaction. The post hoc tests showed that 1) in low job demands, but high job resources employees declared higher job satisfaction, than those who perceived them as medium (p = 0.0001) or low (p = 0.0157); 2) when the level of job demands was perceived as medium, employees with high personal resources declared significantly higher job satisfaction than those with low personal resources (p = 0.0001). Conclusion: The JD-R model can be used to investigate job satisfaction. Taking into account fundamental factors of this model, in organizational management there are possibilities of shaping job satisfaction among employees. Med Pr 2013;64(2):217-225